All‐Inorganic Perovskite‐Based Monolithic Perovskite/Organic Tandem Solar Cells with 23.21% Efficiency by Dual‐Interface Engineering (Adv. Energy Mater. 16/2023). Issue 16 (26th April 2023) - Sun, Shuang‐Qiao; Xu, Xiuwen; Sun, Qi; Yao, Qin; Cai, Yating; Li, Xin‐Yi; Xu, Yan‐Lin; He, Wei; Zhu, Min; Lv, Xuan; Lin, Francis R.; Jen, Alex K.‐Y.; et al.
Abstract : Perovskite/Organic Tandem Solar Cells In article number 2204347, Tingting Shi, Hin‐Lap Yip, Man‐Keung Fung, Yue‐Min Xie, and co‐workers aim to minimize the energy loss of perovskite/organic tandem solar cells (POTSCs) induced by compromised wide‐bandgap perovskite sub‐cells. An ionic liquid, methylammonium formate, is proposed to engineer the top and bottom all‐inorganic perovskite (CsPbI2 Br) interfaces, which leads to passivated perovskite interfacial defects with reconstructed surfaces, therefore, high‐efficiency POTSCs are obtained.